2011
DOI: 10.1097/opx.0b013e3182114320
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Temporal Chordoid Meningioma Causing Compressive Optic Neuropathy

Abstract: This case highlights the importance of prompt diagnosis and treatment, because chordoid meningiomas exhibit a more aggressive biological behavior, with the potential to cause significant morbidity because of mass effect and higher risk of recurrence. To our knowledge, this is the first report of a rare case of a chordoid meningioma in the anterior temporal lobe that presented as a compressive optic neuropathy. The details of this case are presented with a review of relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Nine patients were reviewed from 1743 total meningioma patients in a 1995 to 2013 time period at St. Michael's Hospital in Toronto. To the best of our knowledge, 221 cases of CM have been reported in the English literature worldwide in the form of single case reports and/or case series …”
Section: Discussionmentioning
confidence: 99%
“…Nine patients were reviewed from 1743 total meningioma patients in a 1995 to 2013 time period at St. Michael's Hospital in Toronto. To the best of our knowledge, 221 cases of CM have been reported in the English literature worldwide in the form of single case reports and/or case series …”
Section: Discussionmentioning
confidence: 99%
“…Although sample numbers in the present study were slightly lower than in the series of Couce et al ., the discordance in the MIB‐1 LI raises possible doubts about CM being a malignancy with a truly elevated proliferation potential. Interestingly, it is reported that the MIB‐1 LI was appreciably higher in meningiomas that recurred than those that did not . A recent report suggested that the MIB‐1 LI may be used to predict prognosis in patients with CM, citing the finding that the MIB‐1 LI was increased following tumour recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Only 120 cases of CM have been reported in the English‐language literature since it was first described in 1988 by Kepes et al . Most of those studies focused only on histopathological, immunohistochemical and cytological aspects, and seldom mentioned its clinical features and recurrence …”
Section: Introductionmentioning
confidence: 99%
“…Metastasis, infiltration or physical impingement of tumors into or onto peripheral nerves or nerve roots results in neurological symptoms that may lead to initial diagnosis (1-3). Alternatively, tumor-derived factors or sensitized immunological responses may result in paraneoplastic neurological symptoms that range in severity from mild muscle weakness, gait disturbance and minor sensory loss to profound generalized demyelination and severe pain (4-7).…”
mentioning
confidence: 99%